(untitled) (In situ, 2024)
The islet of Gnalić is located at the southeastern end of the island of Pašman, in front of the southern entrance to the Pašman channel. In 1967, a shipwreck from the end of the 16th century was officially recorded off the islet. After the initial rescue research campaigns, forty-five years later a trial research was carried out, and after excellent results systematic research was initiated which is still ongoing. In the State Archives in Venice, it was confirmed that it was the ship Gagliana grossa, which was launched in Venice in 1569 and sank on the way to Constantinople thirteen years later. The research so far has reached the central part of the ship, where the main frame is located. The underwater excavation yielded a large quantity of ingots of lead white, packed in small barrels, and numerous items from the ship cargo.